Milton's Messiah the son of God in the works of John Milton - Hillier, Russell M. (Oxford : Oxford University Press, 2011)
'Milton's Messiah' provides the first comprehensive book-length analysis of the nature and significance of the Son of God in Milton's poetry and theology. It argues for a radical reassessment of Milton's doctrine of the atonement and its importance for understanding his poetics.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Milton, John, -- 1608-1674 -- Criticism and interpretation; Jesus Christ -- In literature